The Failure of Confidence Mechanism: Reflections on the 1990’s Social Change Movement in the Light of Policy Measures Affecting Farming System in Nepal - Pandey, Tulsi R (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 4,371 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v3i0.1078 Occasional Papers in Sociology and Anthropology Vol.3 1993 p.96-127